1992
DOI: 10.1590/1809-43921992223397
|View full text |Cite
|
Sign up to set email alerts
|

Variação Sazonal De Sulfato, Enxofre Total E Matéria Orgânica No Gênero Humirianthera,em Função Da Idade

Abstract: No período de janeiro a dezembro de 1986 foram coletados 28 (vìnte e oito) espécimens de H. ampla e 09 (nove) de H. rupestris, nas idades adulta e jovem, para determinação dos teores de S04~ e S-total em folha, caule, tubércolo e no solo onde as mesmas se desenvolveram. Em H. ampla o teor de 504~ variou de 0,22-0,78% e em H. rupestris de 0,22-1,30%. O teor de 5 em H. ampla variou de 0,74-0,96% e em H. rupestris de 0,75-1,02%. O teor de S04~em H. ampla obedece a relação folha>tubérculo>caule independente … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The average content of these elements indicated no significant variability dependent on seasonality or physiological age. A study by Varejão et al [ 17 ] evaluated the same organs of the same species, physiological ages, and seasons. They observed that sulfate (SO 4− ) uptake by C. ampla and C. rupestris individually did not depend on seasonality or physiological age.…”
Section: Resultsmentioning
confidence: 99%
“…The average content of these elements indicated no significant variability dependent on seasonality or physiological age. A study by Varejão et al [ 17 ] evaluated the same organs of the same species, physiological ages, and seasons. They observed that sulfate (SO 4− ) uptake by C. ampla and C. rupestris individually did not depend on seasonality or physiological age.…”
Section: Resultsmentioning
confidence: 99%